2011
DOI: 10.1155/2011/824972
|View full text |Cite
|
Sign up to set email alerts
|

A System Out of Breath: How Hypoxia Possibly Contributes to the Pathogenesis of Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular alterations and immunological disturbances and fibrosis, the order of which remains to be fully determined. Clinically, patients show clear signs of hypoxia in skin and internal organs. The low oxygen tension is potentially caused by a yet to be indentified circuitry involving the three features that typify SSc. In addition, once present, the hypoxia creates a vicious circle of ongoing pathology. In this paper, we provide an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…In patients suffering from autoimmune diseases, such as the connective tissue disease systemic sclerosis (SS), the extent of oxidative stress and hypoxia is associated with patient outcome and therapeutic success [9]. Consequently, HIF-1 has become of great interest in the current research in this field, particularly since it has been shown to be involved in persistent pathofibrogenesis and vascular remodeling in SS [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In patients suffering from autoimmune diseases, such as the connective tissue disease systemic sclerosis (SS), the extent of oxidative stress and hypoxia is associated with patient outcome and therapeutic success [9]. Consequently, HIF-1 has become of great interest in the current research in this field, particularly since it has been shown to be involved in persistent pathofibrogenesis and vascular remodeling in SS [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have con rmed that hypoxia could induce EndMT in various diseases, including scleroderma, which contributes to the vicious circle of ongoing pathology, and is considered as an important hallmark in SSc patients [6][7][8][28][29][30]. The Galectin-3, Endothelin-1 (ET-1), HIF-1α/Twist1, BMP-7/Smads and TGFβ1/SMAD signaling pathways have been proven to be critical mediators in PAH by regulating EndMT, and have a critical role in mediating the effect of hypoxia-induced EndMT in pulmonary arterial and cardiovascular remodeling [6,8,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed vascular and neurologic assessment of the lower limb was performed to establish the physiologic health of skin being treated with O 2 -H 2 O. Macrovascular, microvascular and neuro-pathic disease can reduce nutritive blood flow in the skin [4,5] causing lower than normal PskO 2 values. In general, increasing age was associated with some decline in the resistive element (P.I.)…”
Section: Study Participantsmentioning
confidence: 99%
“…Epidermal O 2 to support metabolic function is supplied by O 2 diffusion from the underlying dermal capillary bed or by way of direct O 2 absorption across the stratum corneum from air in contact with the skin surface [1,2]. Cutaneous hypoxia is associated with poor regenerative capacity and can result from altered dermal blood flow due to scleroderma-and diabetic-based microvascular pathology [4,5]. Cutaneous hypoxia is associated with poor regenerative capacity and can result from altered dermal blood flow due to scleroderma-and diabetic-based microvascular pathology [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation